The Comparison and Relationship between Self-Esteem and Physical Fitness in Male and Female Students of University of Tehran - Fazollah Ghods; Homaila Takali; Mortaza Abdollahi; Hasan Gharayagh Zandi; Marziyeh Mashhouri; Sanam Ghods (University of Tehran, 2010)
This study examined the relationship between physical fitness and self-esteem in non - physical education students. 109 female and 225 male students who took general physical education course (1). The students completed Cooper - Smith questionnaire and their scores of general physical education course. The mean score of physical fitness for male students was 17.4 and for female students 19.1. The mean score of the self - esteem for females was 33.1 and for males 35.2. There was no significant relationship between the level of self-esteem and physical fitness (p>0.05). In general, findings of this research like many previous studies indicated a lower level of self-esteem in females compared with males. Also, it seems that physical fitness during the general physical education course has no relationship with students' evaluation of their own capabilities (self - esteem).